Implementasi Fuzzy Dalam Menentukan Dampak Belajar Online Pada Masa Pandemi Covid-19 - Fahrija Azzahra; N Nurhayati; Yuli Sartika Nasution; Sri Ramadani; Agus Perdana Windarto (STMIK Budi Darma, 2020)
The purpose of this study was to identify the impact of online learning during the Covid-19 pandemic. As we know that the epidemic caused by a virus called corona has an impact on all aspects of people's lives, especially education. Teaching and learning activities that are usually done directly must also be stopped and replaced with online learning at home. In determining the impact of online learning the need for a support system, where the support system used is the Fuzzy Tsukamoto method with 4 variables namely tasks, costs, networks and the impact of online learning during the Covid-19 pandemic. For the calculation of data will go through stages of fuzzification, inference, and defuzzification. Identification is done by entering existing parameters so that conclusions can be obtained how big the impact of online learning during the Covid-19 pandemic.Keywords: Fuzzy Tsukamoto, Dampak Belajar Online, Pandemi Covid-19